Accumulated precipitation and air density are linked to termite (Blattodea) flight synchronism in a Seasonally Dry Tropical Forest in north‐eastern Brazil. Issue 1 (1st December 2021) - Lucena, Emanuelly F; Silva, Israel S; Monteiro, Sara R P; Moura, Flávia M S; Vasconcellos, Alexandre
Abstract: Termite dispersal flights (Blattodea: Termitoidae) are influenced by several factors that are intrinsic and extrinsic to colonies and vary according to the environment and target species. This study aimed to evaluate the main characteristics of the dispersal flights of a termite community and the environmental variables related to these flights in a Seasonally Dry Tropical Forest, situated in the semiarid region of north‐eastern Brazil. The alates were collected with trays placed on the ground. Sampling was carried out over a year, with weekly trap reviews. Flight peaks started in February; i.e. these events were more frequent and alates from all species were captured. The trays were checked daily for 40 days during this period. A principal coordinate analysis was performed to determine the response variables and, after that, a generalised linear model was performed to analyse the relationship between these variables and environmental variations. Alates of 37 species were captured and the community flight pattern proved to be synchronised and highly temporally concentrated, regardless of family, subfamily or even genera. The daily sampling analysis showed that 97% of species flights occurred between the 13th and 33rd days following the start of the 40 days of daily revisions. The number of flight occurrences and species composition were significantly influenced by the accumulated precipitation over 72 h and air density. The latter variable was evaluated for the first time in this type of study. The high synchronism between species may be related to the brief period in which arid and semiarid ecosystems have the correct conditions for alate flights, which is different to alate flight occurrence in tropical rainforests, where the environmental conditions usually allow termites to fly throughout the entire year.